2007
DOI: 10.1128/mcb.02293-06
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor I X Deficiency Causes Brain Malformation and Severe Skeletal Defects

Abstract: The transcription factor family of nuclear factor I (NFI) proteins is encoded by four closely related genes: Nfia, Nfib, Nfic, and Nfix. A potential role for NFI proteins in regulating developmental processes has been implicated by their specific expression pattern during embryonic development and by analysis of NFI-deficient mice. It was shown that loss of NFIA results in hydrocephalus and agenesis of the corpus callosum and that NFIB deficiency leads to neurological defects and to severe lung hypoplasia, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(151 citation statements)
references
References 73 publications
7
143
0
Order By: Relevance
“…We note that mice deficient in Nfix function show, in addition to brain abnormalities, a kyphotic deformation of the spine and impairment of endochondral ossification in the vertebrae and femur. 15,16 There have been no reports of neoplasia in the condition to date. The small number of cases reported to date hinders identification of genotype-phenotype correlations for NFIX.…”
Section: Molecular Resultsmentioning
confidence: 99%
“…We note that mice deficient in Nfix function show, in addition to brain abnormalities, a kyphotic deformation of the spine and impairment of endochondral ossification in the vertebrae and femur. 15,16 There have been no reports of neoplasia in the condition to date. The small number of cases reported to date hinders identification of genotype-phenotype correlations for NFIX.…”
Section: Molecular Resultsmentioning
confidence: 99%
“…29 Nfix-deficient mice show enlargement of the lateral and third brain ventricles and partial agenesis of the corpus callosum; in addition, they show kyphotic deformation of the spine and impaired endochondral ossification in the vertebrae and femur. 29 The case of Lysy et al 4 showed kyphosis, artogryphosis of lower limb craniosynostosys and moderate ventriculomegaly; 4 Auvin et al 5 reported advanced bone age. As our case 3 does not show any of these malformations, the phenotype associated with NFIX haploinsufficiency may occur with variable penetrance.…”
Section: Discussionmentioning
confidence: 99%
“…Nfix mutants present an overexpansion of the embryonic brain and a delay of hippocampal progenitor differentiation that are not seen in other Nfi mutants (Driller et al 2007;Campbell et al 2008;Heng et al 2012b). Moreover, manipulation of Nfia expression alongside that of Nfix in NS cells shows that the two genes have different activities in the cells, and Nfia does not have a prominent role in the regulation of quiescence (B Martynoga, unpubl.).…”
Section: Nfix Targets Cell Adhesion and Ecm Genes To Promote Ns Cell mentioning
confidence: 99%